Chemical Characteristics of Linum usitatissimum Sub. Species Humil and Usitatissimum - Arshadi, Sattar; Hasanzadeh, Abdollah; Ranjzad, Masoma (Asian Journal of Chemistry, 2010)
Flax seed species is oil seed that has oil percentage with a good quality of w-3 essential fatty acids. Linum usitatissimum (crop species of Linum genus) has two sub species. The aim of this study is to introduce better sub species for agricultural purposes. Important characteristic of this species including: 1000-seed weight, seed weight/plant weight, oil content, protein content and fatty acid components were measured. Oil and protein content based on dry seed was measured using the extraction by Ether and Lowry method. Sub. sp humile had more 1000 seed weight, seed weight/plant weight, oil content and, sub. Sp usitatissimum had more protein content. Analysis of variation revealed the existence of significant variation at 1 and 5 % level of significance for oil and protein content, respectively. The amounts of the five fatty acids namely, palmitic acid, stearic acid, oleic acid, linolenic acid and linoleic acid were detected and measured by gas chromatography. Analysis of variance showed the existence of significant variation for all five fatty acids at 1 % level of significance, too. Two studied sub species were different in measured characteristic, completely. Mostly investigated characteristics belonged to sub. Sp. humile, except protein content.